IMPLEMENTATION OF INTERNATIONAL INSTRUMENTS IN INDONESIAN LEGISLATION IN THE FIELD OF CONSERVATION OF FISH RESOURCES - HASAN, YULIA A. (Journal of Humanity, 2015)
The intention contained in laws and regulations concerning the conservation of fish resources is so that there are activities that lead to protection of fish resources as a whole. During this time the utilization of fish resources more dominant done compared to the protection and preservation, so the impact on the aquatic ecosystem. The purpose of this research is to examine international agreements regarding the conservation of fish resources which have been ratified and implemented into other policies and legislation in order to become a guideline in behavior so bring a change in society. This research is a descriptive qualitative using a data source from an earlier study results and document the latest libraries. Results of the study that the conditions of the CCRF (Code of Conduct for Responsible Fisheries) became a legal basis in the formulation of the provisions concerning the management of fish resources responsibly. Sustainable fisheries zone were never regulated in the regulation of the management of conservation areas. The Fisheries Act has yet to implement the provisions of the UN fish stocks agreement of 1995 relating to the conservation and management of fish resources in the ZEE and Indonesia on the high seas. Therefore the Fisheries Act require refinement, considering Indonesia has been a member of two regional fisheries management organization and ratify the UNITED NATIONS Agreement on fish stocks of 1995.